American Board of Orthopaedic Surgery's Initiatives Toward Competency-Based Education. Issue 2 (19th April 2022) - Van Heest, Ann E.; Armstrong, April D.; Bednar, Michael S.; Carpenter, James E.; Garvin, Kevin L.; Harrast, John J.; Martin, David F.; Murray, Peter M.; Peabody, Terrance D.; Saltzman, Charles L.; Saniei, Mona; Taitsman, Lisa A.; et al.
Abstract: The American Board of Orthopaedic Surgery (ABOS) is the national organization charged with defining education standards for graduate medical education in orthopaedic surgery. The purpose of this article is to describe initiatives taken by the ABOS to develop assessments of competency of residents to document their progress toward the independent practice of orthopaedic surgery and provide feedback for improved performance during training. These initiatives are called the ABOS Knowledge, Skills, and Behavior Program. Web-based assessment tools have been developed and validated to measure competence. These assessments guide resident progress through residency education and better define the competency level by the end of training. The background and rationale for these initiatives and how they serve as steps toward competency-based education in orthopaedic residency education in the United States will be reviewed with a vision of a hybrid of time and competency-based orthopaedic residency education that will remain 5 years in length, with residents assessed using standardized tools.